Impact of C-reactive protein on osteo-/chondrogenic transdifferentiation and calcification of vascular smooth muscle cells - Henze, Laura A.; Luong, Trang T.D.; Boehme, Beate; Masyout, Jaber; Schneider, Markus; Brachs, Sebastian; Lang, Florian; Pieske, Burkert; Pasch, Andreas; Eckardt, Kai-Uwe; Voelkl, Jakob; Alesutan, Ioana (Aging-Us, 2019)
Medial vascular calcification occurs during the aging process and is strongly accelerated by chronic kidney disease (CKD). Elevated C-reactive protein (CRP) levels are associated with vascular calcification, cardiovascular events and mortality in CKD patients. CRP is an important promoter of vascular inflammation. Inflammatory processes are critically involved in initiation and progression of vascular calcification. Thus, the present study explored a possible impact of CRP on vascular calcification. We found that CRP promoted osteo-/chondrogenic transdifferentiation and aggravated phosphate-induced osteo-/chondrogenic transdifferentiation and calcification of primary human aortic smooth muscle cells (HAoSMCs). These effects were paralleled by increased cellular oxidative stress and corresponding pro-calcific downstream-signaling. Antioxidants or p38 MAPK inhibition suppressed CRP-induced osteo-/chondrogenic signaling and mineralization. Furthermore, silencing of Fc fragment of IgG receptor IIa (FCGR2A) blunted the pro-calcific effects of CRP. Vascular CRP expression was increased in the klotho-hypomorphic mouse model of aging as well as in HAoSMCs during calcifying conditions. In conclusion, CRP augments osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells through mechanisms involving FCGR2A-dependent induction of oxidative stress. Thus, systemic inflammation may actively contribute to the progression of vascular calcification.
CRIS-Team Scopus Importer:2019-08-30
Keywords: CKD; CRP; Osteo-/chondrogenic signaling; Oxidative stress; Vascular calcification; Vascular smooth muscle cells